1983
DOI: 10.1051/rnd:19830710
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of phosphorus and calcium and minimal maintenance requirement for phosphorus in growing sheep fed a low-phosphorus diet

Abstract: Summary. This paper reports the effects of a marginal phosphorus deficiency associated or not with an excess of calcium in 5 lots of 4 growing sheep each fed a semi-purified diet containing cellulose (25-27 %) and urea as the only nitrogen source.In experiment 1, two P-deficient diets (1.2 g/kg DM) poor (LPLCa) or rich (LPHCa) in Ca led to lower phosphatemia, decreased appetite and a negative or zero P balance. The effects of P deficiency were amplified by excess Ca.In experiment 2, two diets containing 1.5 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
4
11
0
2
Order By: Relevance
“…Tables 3 and 6 show that P deficiency grossly reduced plasma P ; concentrations and tended to increase Ca concentrations, whereas low Ca intake had no influence on plasma Ca and gave a non-significant rise to P ; concentration. These findings fully agree with published results (Young et ah, 1966;Perge et al, 1982;Boxebeld et al, 1983;Braithewaite 1985;Schneider et al, 1985;Breves et al, 1987;Corlett and Care 1988;Rodehutscord et al, 1994;Pfeffer et al, 1995). Only when Ca concentration of dietary dry matter was reduced to less than 1 g/kg, Field et al, (1975) observed reductions in plasma Ca concentrations of lambs.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Tables 3 and 6 show that P deficiency grossly reduced plasma P ; concentrations and tended to increase Ca concentrations, whereas low Ca intake had no influence on plasma Ca and gave a non-significant rise to P ; concentration. These findings fully agree with published results (Young et ah, 1966;Perge et al, 1982;Boxebeld et al, 1983;Braithewaite 1985;Schneider et al, 1985;Breves et al, 1987;Corlett and Care 1988;Rodehutscord et al, 1994;Pfeffer et al, 1995). Only when Ca concentration of dietary dry matter was reduced to less than 1 g/kg, Field et al, (1975) observed reductions in plasma Ca concentrations of lambs.…”
Section: Discussionsupporting
confidence: 95%
“…Although very high rates of Ca intakes seem to be without negative effects on lambs (Young et al, 1966) or dairy goats (Deitert and Pfeffer, 1993;Pfeffer et al, 1993) fed on reduced levels of P, excesses of Ca have been found to amplify negative effects of P deficiency in growing lambs (Boxebeld et al, 1983) and kids (Pfeffer et al, 1995).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Mejia-Haro et al (2001) found no differences in the apparent absorption and retention of P in 6-month old lambs fed a diet slightly deficient in P and Ca:P ratios of 2.5:1.5, 6:1 and 9:1. However, Boxebeld et al (1983) observed in 6-month old lambs fed semipurified diets that the negative effects of a P marginal deficiency (decreased phosphatemia and DMI) got worse when Ca was supplied to get a Ca:P ratio equal to 9.1:1. Also, Wan zahari et al (1990) observed in wether lambs grown from 25 to 50 kg BW that a Ca:P ratio of 3.6:1 had a negative effect on intake and growth rate when P was supplied at 0.75 times its requirement.…”
Section: Calcium and Phosphorusmentioning
confidence: 99%
“…Some studies have showed that dietary Ca has little effect on voluntary DMI or mobilisation of P (Ternouth and Sevilla, 1990;Bortolussi et al, 1992) and that high Ca:P ratios have no effect on P utilisation in lactating ruminants as long as P is adequate (Deitert and Pfeffer, 1993;de Waal and Koekemoer, 1997). Other research, however, has demonstrated that high a Ca:P ratio has a negative effect (Boxebeld et al, 1983;Pfeffer et al, 1995). In Australian studies, high Ca:P ratios, resulting from high Ca concentrations in stylo-dominated pasture, has important consequences: changes in faecal P, P i , bone thickness and live weight gain for beef cattle (Winter, 1988;Coates, 1994).…”
Section: Control Of Phosphorus Homeostasis and The Interaction Of Calmentioning
confidence: 99%